2011
DOI: 10.1530/joe-10-0480
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of sex steroid action: the role of micro-RNAs and FOXO transcription factors in cycling endometrium and cancer

Abstract: The rise and fall in ovarian oestrogen and progesterone production orchestrates a series of events that are indispensable for reproduction, including ovulation, implantation, decidualisation and menstruation. In the uterus, these events involve extensive tissue remodelling, characterised by waves of endometrial cell proliferation, differentiation, recruitment of inflammatory cells, apoptosis, tissue breakdown, menstruation and regeneration. The ability of ovarian hormones to trigger such diverse physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 127 publications
1
39
0
Order By: Relevance
“…Endometriosis associated miRNAs may have regulatory functions in hypoxia, inflammation, tissue repair, TGF-β regulated pathways, cell growth, cell proliferation, apoptosis, extracellular matrix remodeling and angiogenesis . It has been proposed that miRNAs may be associated with malignant transformation (Lam et al, 2012).…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…Endometriosis associated miRNAs may have regulatory functions in hypoxia, inflammation, tissue repair, TGF-β regulated pathways, cell growth, cell proliferation, apoptosis, extracellular matrix remodeling and angiogenesis . It has been proposed that miRNAs may be associated with malignant transformation (Lam et al, 2012).…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…Dysregulated E2 metabolism has been reported to contribute to a variety of human diseases including leiomyoma, endometriosis, osteoporosis, Parkinson disease, and gynecological malignancies (31)(32)(33)(34)(35). Recently, Flamini et al (36) reported that E2 could regulate endometrial cell cytoskeletal remodeling and motility via focal adhesion kinase.…”
Section: Anxa2 Knockdown Compromises Growth Metastasis and Proangiomentioning
confidence: 99%
“…In addition, Hh signaling regulates whole‐body energy metabolism via activating the Akt/FOXO pathway (Zhang, Cheng, Wang, Leung & Mak, 2017) and also influences IIS activity in certain developmental events (Lipinski et al., 2005). This is particularly interesting as in mammals, IIS is implicated in the sex‐specific regulation of tissue differentiation (Lam, Shah & Brosens, 2012; Pitetti et al., 2013). These data prompted us to perform an in silico analysis of the human genome for the presence of conserved GLI binding sites in the FOXO3 locus (Figures S11 and S12).…”
Section: Discussionmentioning
confidence: 99%